Break even analysis of pdkv uv-assisted treatment device for post harvest decay control of nagpur mandarin Fruits in India (Bangladesh Journal of Botany, 2026)
Nagpur Mandarins has GI-tag for Nagpur region of India and occupy 135,000 ha area in Maharashtra, the leading producer of this Vitamin-C rich delicious fruit. Due to 20-30% losses caused by fungal rots fruits are coated with edible wax to improve their shelf life. Despite rich taste Nagpur Mandarins are not getting enough international market space due to seeds and fungicide residues contributed by field sprays and wax coatings. This constraint is removed by developing “PDKV UV-Assisted Treatment Device” for fungicide free post-harvest disease management of Nagpur Mandarins. UV-treatment reduces fungal diseases by surface sterilization of fruits and by improving their innate immunity by ‘hormesis’. Break even analysis of this machine shows the potential to provide viable business to mandarin processing units. This business gives higher benefit beyond breakeven point by lower initial investment and higher throughput capacity; and has a higher margin of safety in quantitative and monetary terms.Bangladesh J. Bot. 55(1): 217-222, 2026 (March)